SUFIKS DERIVASIONAL YANG MENYATAKAN TEMPAT DALAM KOMIK CHIBIMARUKO CHAN JILID 2 KARYA SAKURA MOMOKO - Tariasih, Ni Kadek Loji (Humanis; Volume 6. No. 1. Januari 2014)
kura Momoko’s Comic Chibimaruko Chan Vol 2. The data were analyzed based on Morphology Theory by Francis Katamba. The results of the analysis show that some derivational suffixes indicating the place, such as suffix –ba (?), –kan (?), –shitsu (?), and –ya (?). Suffix –ba (?) and –shitsu (?) change the word class of verb into nouns. Suffix –kan (?) causes a shift in the sub-class of a word of nomina abstract into nomina concrete. Suffix –ya (?) changes the meaning. In the meaning, suffix –ba (?), – kan (?), –shitsu (?), and –ya (?) refer to place of day to day activities, a large building, room, and point of sale.
Keywords: Derivational Suffixes, Word Class, Meaning